Keefektifan Model Discovery Learning terhadap Kemampuan Membaca Pemahaman Siswa Kelas VIII tingkat SMP - Nuraeni, Ida; Arly, Arly; Risvirenol, Risvirenol (Jurnal Bahasa dan Sastra, 2024)
The primary issue addressed in this study pertains to the limited reading proficiency among students in class VIII at SMPN 1 Tikke Raya. The objective of this study is to assess the effectiveness of the discovery learning model in enhancing the reading and comprehension skills of these students. To evaluate the students’ reading comprehension abilities, this study analyzes their comprehensive understanding at factual, interpretative, and applicative levels, as defined by Ruddell’s Taxonomy. The study adopts an experimental design, employing a pretest-posttest Nonequivalent Control Group Design. The study population comprises 72 students, with a sample size of 48 students allocated to both the experimental and control groups. The data collection for this study includes reading ability and comprehension tests, as well as observations of students’ attitudes and skills during the intervention period. At the pretest stage, the results indicate no significant variation between the control and experimental groups, with the control group obtaining an average score of 42.29 and the experimental group achieving an average score of 45.00. However, the posttest findings reveal a disparity between the control and experimental groups, with the control group averaging 52.71 and the experimental group averaging 56.04. The data analysis yields a significance value of 0.453. Considering a significance level of 0.05 in the Mann-Whitney test, the Discovery Learning model is deemed ineffective in influencing the reading abilities of the students under examination.